2022
DOI: 10.1002/fsn3.2814
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive content and phenolic compounds of common medlar (Mespilus germanica L.) and Stern’s medlar (M. canescens Phipps)

Abstract: Medlar (Mespilus) is an important fruit and is rich in nutritional and medical properties. Bioactive content and phenolic compounds of leaf, fruit, and seed samples of common medlar (M. germanica) and Stern’s medlar (M. canescens) were studied. The coefficient of variation showed high values among all the characters and was more than 50.00%, ranging from 59.74 to 196.81%. The leaf of M. canescens showed the highest total phenolic content (14.73 mg/g dry weight, DW) and followed by 13.70 mg/g DW in the seed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Chlorogenic acid (19.81 mg/kg FW) and cryptochlorogenic acid (11.3 mg/kg FW), pertaining to the group of phenolic acids, were also identified, as were four different coumaroylquinic acids, two feruloylquinic acids, sinapic acid, protocatechuic acid, and ellagic acid. Other authors [9,10,15] have also detected ferulic acid, p-coumaric acid, caffeic acid, and gallic acid in medlar. S1.…”
Section: Content Of Sugars Acids and Phenolic Compounds In Fresh Tech...mentioning
confidence: 89%
See 1 more Smart Citation
“…Chlorogenic acid (19.81 mg/kg FW) and cryptochlorogenic acid (11.3 mg/kg FW), pertaining to the group of phenolic acids, were also identified, as were four different coumaroylquinic acids, two feruloylquinic acids, sinapic acid, protocatechuic acid, and ellagic acid. Other authors [9,10,15] have also detected ferulic acid, p-coumaric acid, caffeic acid, and gallic acid in medlar. S1.…”
Section: Content Of Sugars Acids and Phenolic Compounds In Fresh Tech...mentioning
confidence: 89%
“…Medlar fruits are rich in bioactive compounds, are a good source of natural antioxidants, and are consequently often used in traditional folk medicine to relieve various problems [ 3 , 4 , 9 , 10 , 11 ]. To illustrate, numerous studies have reported that phenolic compounds are responsible for the curative effects of different fruit species since they exert a positive effect on reducing chronic disease incidence [ 6 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%